2014
DOI: 10.14341/probl201460610-13
|View full text |Cite
|
Sign up to set email alerts
|

The levels of immunoreactive proteins and cytokines in the blood of the patients presenting with autoimmune thyroid diseases

Abstract: We determined the levels of TSH, free T4 (fT4), immunoregulatory proteins (alpha-2-macroglobulin (α2-MG), lactoferrin (LF), alpha-1-antitripsin (α1-AT) , and cytokines (TNF-alpha, IL-6, IFN-gamma)) in the blood of 50 women presenting with diffuse toxic goiter (DTG) and 35 women with autoimmune thyroiditis (AIT) before and 4-6 months after the treatment. Thirty healthy women served as controls. Hypothyroidism in the outcome of AIT was associated with hypercytokinemia and the enhanced levels of a2-MG and LF, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The data available in the literature are not entirely clear. For example, Maklakova et al reported about an increased content of immunoregulatory α2-MG in AIT hypothyroidism; the content of α2-MG remained elevated even after achieving the euthyroid state, which could be regarded as a risk factor for relapse [22]. In another study by Maklakova et al an increase in α2-MG levels has been demonstrated in newly diagnosed or recurrent Graves' disease [23].…”
Section: Discussionmentioning
confidence: 97%
“…The data available in the literature are not entirely clear. For example, Maklakova et al reported about an increased content of immunoregulatory α2-MG in AIT hypothyroidism; the content of α2-MG remained elevated even after achieving the euthyroid state, which could be regarded as a risk factor for relapse [22]. In another study by Maklakova et al an increase in α2-MG levels has been demonstrated in newly diagnosed or recurrent Graves' disease [23].…”
Section: Discussionmentioning
confidence: 97%